The Lviv Agglomeration as a Growth Pole in the Spatial Development of the Carpathian Region of Ukraine - Leshchukh, Iryna (Global Prosperity, 2026)
Abstract. The article examines the role of the Lviv agglomeration as a growth pole in shaping the spatial structure and socio-economic dynamics of Ukraine’s Carpathian region. It is substantiated that the agglomeration concentrates a disproportionately large share of the region’s demographic, economic, infrastructural, innovative, and educational-scientific potential, thereby performing the function of its system-forming core. Based on the analysis of demographic indicators, business activity, income levels, investment attractiveness, transport and logistics infrastructure, innovation and cluster specialization, as well as the concentration of intellectual capital, it is demonstrated that the Lviv agglomeration generates strong agglomeration effects that determine the hierarchy of spatial development in the Carpathian region. It is established that these effects are manifested not only in the growth of productivity and investment activity in the core, but also in the formation of regional labour markets, educational and logistics networks that extend to surrounding territories. At the same time, the lack of institutionally formalized mechanisms of inter-municipal coordination and polycentric governance limits the transmission of positive agglomeration effects to semi-peripheral and peripheral areas, particularly mountain communities. It is concluded that the potential of the Lviv agglomeration as an instrument of regional convergence can be realized only through a transition from spontaneous agglomeration dynamics to an institutionally structured polycentric model of spatial development aimed at strengthening horizontal inter-territorial linkages and reducing intra-regional disparities.